Depth-resolved cathodoluminescence in γ/β-Ga2O3 polymorph junctions - E. B. Yakimov; E. E. Yakimov; A. Y. Polyakov; A. A. Vasilev; I. V. Schemerov; A. Kuznetsov; S. J. Pearton (APL Materials)
The dominant emission bands were assessed in γ/β-Ga2O3 polymorph junctions for the first time, using depth-resolved cathodoluminescence. By comparing our results collected from the γ-Ga2O3 films with literature data available for β-Ga2O3, we conclude that the emission properties for these Ga2O3 polymorphs are rather similar, and the origin of this emission may be tentatively assigned to the recombination involving the conduction band electrons and self-trapped holes or Ga vacancy acceptors. In particular, the most prominent emissions peaked around 2.4 and 2.9 eV bands, and two minor bands peaked at 2.6 and 2.8 eV. Importantly, these band positions were not affected by subsequent irradiation of γ-Ga2O3 upon its formation via disorder-induced ordering. On the other hand, the intensities of these bands are greatly enhanced by increased electron concentration supplied by donors introduced into γ-Ga2O3 by hydrogen plasma treatment. These data add to the understanding of emission properties in Ga2O3 polymorphs.